Tekst poetycki jako materiał źródłowy do poznania modernistycznych sposobów konceptualizacji świata (na przykładzie analizy semantycznej leksemu dziewanna) - Kuryłowicz, Beata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
The present article discusses the role of poetic texts in recreating and reestablishing modernist means for the conceptualization of the world. The article has been divided into two parts. The first part is to present the theoretical considerations on the participation of poetic materials in revealing the meaning of lexical units and the world’s conceptualization generated by a language lexicon. The other part includes a semantic analysis of the lexeme dziewanna (mullein), whose conceptual model has been reconstructed on the basis of modernist poetic texts. The analysis of artistic texts has made it possible to demonstrate conceptually the fundamental, though not attested in systemic facts, special features of the lexeme: [dziewanna] “has golden and yellow leaves”, “has a long and straight stem”, “is tall” and “blooms in summer”. Poetic texts also attest to the attribution “grows on barren land”, which has been preserved in the Polish proverb: Gdzie rośnie dziewanna, tam bez posagu panna (literally: [homestead] where mullein grows is where a portionless maid lives) All considerations done so far also indicate that the most important place within the conceptual framework of the word is occupied by the elements that belong to the domain: PHYSICAL FEATURES, and the range of colour characteristics in particular. These elements form a strong part of the semantic core of the name and determine numerous connotations such as: “beauty”, “perfectness”, “brightness”, “purity”, “joy”, “vitality”, “biological determination”, “joy of living”, “youth” and “health”, “fertility of nature”, “fertility”, “abundance”, “richness”, “eroticism” and “sexual appeal”. The conventionalized character of the elements of the sub-framework: PLACE OF GROWTH – “grows on sands, waste grounds”, “grows in desolate places” influences the relatively well-developed structure of this section of the conceptual model of the word. The environmental features of the name justify, in turn, the following connotations: “penury”, “loneliness” and “abandonment”. Its locative characteristics also includes the image of the flower in which the connotations such as “heroic loneliness”, “perseverance despite the odds” come into the foreground.